1986
DOI: 10.1111/j.1741-2358.1986.tb00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assessed General Health and Dental Status Among the Elderly in a Swedish County

Abstract: A random sample of non‐institutionalized elderly people in Örebro County, Sweden, has been examined. The present paper reports on the general health conditions obtained from interviews in this population and on the relation between general health and dental status. Eighty‐one percent of the clinically examined subjects considered that they were healthy or fairly healthy. A higher percentage of women as compared to men regarded themselves to be moderately or very ill. Women also used more drugs than men did. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…Older persons with physical disability were at significantly increased risk of current decay and edentulism but at no increased risk of periodontal disease compared with their physically able counterparts. This finding is consistent with previous research that has identified an association of chronic health conditions with oral disease in older persons 16,17 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Older persons with physical disability were at significantly increased risk of current decay and edentulism but at no increased risk of periodontal disease compared with their physically able counterparts. This finding is consistent with previous research that has identified an association of chronic health conditions with oral disease in older persons 16,17 …”
Section: Discussionsupporting
confidence: 93%
“…We further determined that mobility disability was a strong predictor of recency of last dental visit; that is, the more disabled were less likely to have seen a dentist recently. The relationship between mobility disability and dental utilization, which has been reported by others, 17–19 lends further support to the interpretation that mobility disability affects an older person's risk of edentulism by restricting access to necessary dental care.…”
Section: Discussionsupporting
confidence: 65%
“…There is general agreement that elderly people, if they have natural teeth and if they are aware of a dental problem, will seek and use dental services in a manner similar to younger adults (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). It is not so clear, however, how other factors influence this behavior.…”
mentioning
confidence: 99%
“…A mixed picture emerges. A Swedish study [Palmqvist et al, 1986] finds self-assessed general health significantly correlated with dental status. On the other hand, Mac-Entee et al [1985] found no relationship between systemic health and oral disorders in the elderly in a Canadian nursing home, but they go on to say that ".…”
Section: Systemic Healthmentioning
confidence: 99%
“…Various authors have emphasized the effects on food choice that changes in masticatory efficiency produce. It will also be recalled that full denture prostheses also produce mucosal changes which in turn affect taste and food choice and selection [see Papas et al, 1988].…”
Section: Studies On Masticatory Functionmentioning
confidence: 99%